2021
DOI: 10.3389/fnbot.2021.619504
|View full text |Cite
|
Sign up to set email alerts
|

A Database for Learning Numbers by Visual Finger Recognition in Developmental Neuro-Robotics

Abstract: Numerical cognition is a fundamental component of human intelligence that has not been fully understood yet. Indeed, it is a subject of research in many disciplines, e.g., neuroscience, education, cognitive and developmental psychology, philosophy of mathematics, linguistics. In Artificial Intelligence, aspects of numerical cognition have been modelled through neural networks to replicate and analytically study children behaviours. However, artificial models need to incorporate realistic sensory-motor informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Deep learning architectures allow the efficient building of many layers of information processing stages in deep architectures. They benefit pattern classification and learning characteristics or representations [19,20]. Deep learning architectures, such as deep belief networks (DBNs) and convolutional deep neural networks, have obtained impressive results in several areas.…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning architectures allow the efficient building of many layers of information processing stages in deep architectures. They benefit pattern classification and learning characteristics or representations [19,20]. Deep learning architectures, such as deep belief networks (DBNs) and convolutional deep neural networks, have obtained impressive results in several areas.…”
Section: Related Workmentioning
confidence: 99%
“…Papers that use artificial intelligence techniques to identify writing problems in children, such as [14], point out that they use an artificial neural network to develop a classification model for detecting developmental dysgraphia in children. The results showed that the model was approximately 93% accurate in detecting dysgraphia.…”
Section: Review Of Related Workmentioning
confidence: 99%